El comercio exterior de México en el TLCAN y el bienestar social: un análisis desde la perspectiva de dinámica de sistemas - Naranjo Juárez, Adriana (Universidad Michoacana de San Nicolás de Hidalgo, 2012)
This investigation, looks for to give answer to the existent discussion, about the benefits that he/she has had or he/she has stopped to have the commercial exchange that Mexico has sustained starting from the signature of the Treaty of Free Trade of America of the North (TLCAN), in the population's well-being. Different theories, talk about the advantages of the international trade for the countries, arguing that the specialization, the division of the work and the biggest productivity, elevate the well-being of the countries, since they reach a bigger production a smaller cost. To weigh, that the trade wide external production opportunities and of consumption for the involved countries, the discussion about their continuous effective benefits, since a good negotiation of the treaties of free trade (TLC .s) has not existed, also, of the lack of support of the State and of a correct regulation that guarantees earnings for the involved countries.

Esta investigación, busca dar respuesta a la discusión existente, sobre los beneficios que ha tenido o ha dejado de tener el intercambio comercial que México ha sostenido a partir de la firma del Tratado de Libre Comercio de América del Norte (TLCAN), en el bienestar de la población. Diferentes teorías, hablan sobre las ventajas del comercio internacional para los países, argumentando que la especialización, la división del trabajo y la mayor productividad, eleva el bienestar de los países, ya que alcanzan una mayor producción a un menor costo. A pesar, de que el comercio exterior amplia oportunidades de producción y de consumo para los países involucrados, la discusión sobre sus beneficios continua vigente, ya que no ha existido una buena negociación de los tratados de libre comercio (TLC ?s), además, de la falta de apoyo del Estado y de una correcta regulación que garantice ganancias para los países involucrados.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias en Comercio Exterior
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2012-0007; Política monetaria; Apertura comercial; Demanda; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/962